Blended Learning: Strategi Meningkatkan Kualitas Perkuliahan dengan Aplikasi Google Meet pada Mahasiswa Prodi Bimbingan dan Konseling Islam - M. Zainul Arifin; Sabarudin Sabarudin; Alfin Miftahul Khairi; Dewi Lestariningsih (JEID: Journal of Educational Integration and Development, 2022)
The purpose of this study was to improve the quality of learning in activating and motivating students with the blended learning model. This research was conducted with an action approach in a collaborative manner with civil servants and students. The type of research used in this research is development research using a qualitative approach. Data were obtained using observation techniques with the aim of knowing the actual conditions in the field, interview techniques were carried out by researchers with lecturers and students to find out the implementation of activities during the course of the activity, and questionnaires, namely the lecture quality questionnaire using the google meet application. The number of questions consists of 10 multiple choice items followed by all of BKI students 5th grade  C.  The results showed that lectures with the blended learning model with the google meet application could improve the quality of lectures for Islamic guidance and counseling students. students are more active when lectures take place, mastery of the material is better and more confident in conveying opinions. Therefore, the Google Meet application by providing gradual actions is considered very useful to support the implementation of blended learning.